(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Most authors of post-colonial diasporic origin tend to write in a formulaic fashion. Inviting readers from all over the world, they use methods as varied as stream of consciousness, immigration, magic realism, alienation, and the capacity to adjust to a new area and culture. The literary world has taken notice of Indian literature in English because of the depth and relevance of its subject matter. The contemporary trend in Indian writing in English is unparalleled, despite the fact that outstanding literary works written in English were discovered a century ago. Numerous authors have gained widespread recognition on both a national and international scale. Some of the most well-known Indian authors of the modern era did not even grow up in India. Modern Indian English literature found a strong ally in India’s female authors. They have shed light on many of the ongoing problems that women have had to deal with for centuries. Women who have stepped out to demonstrate their efficacy in numerous fields have been met with resistance from patriarchal culture. An identity crisis does not arise from one specific event or cause. A person’s identity crisis may have been brought on by a number of different things.